Barbas y barbudos en la toponimia española y extremeña - Manuel Mañas Núñez (Anuario de Estudios Filológicos)
Linguistic study of some Spain and Extremaduran place names that begin with the lexeme barb-. It is concluded that they derive from the Indo-European root *bar-b-, with different orographic and hydronymic meanings: ‘elevation’, ‘deep valley’, ‘flat floodable terrain’ and even ‘springing water’.